Collaborative Governance in the Development of a Chinese Java Acculturation Tourism Village in Besani Blado Village - Slamet Ali Puji; Hendy Setiawan; Yendra Erison (Indonesian Journal of Social Sciences, Policy and Politics, 2024)
This research aims to discuss the concept of collaborative governance in handling the development of cultural acculturation tourism villages in Besani Blado Batang Village. Carrying out tourism programs is the main responsibility of the public sector, private sector, and community sector so that the Javanese-Chinese acculturation tourism village of Besani Village can run optimally. Besani Village has a superior tourist spot, namely De Blado. This research is qualitative research with descriptive methods. Data collection techniques used were interviews, documentation, and observation. This research aims to find out to what extent collaborative governance techniques can build a better Javanese Chinese acculturation tourism village in Besani Village. In this research, results were obtained where the public sector, private sector, and community sector provided good support. The value of collaboration shown by all sectors succeeded in making the Javanese Chinese acculturation tourism village Besani Village become one of the new tourist village destinations which has shot up very quickly since its establishment in 2022. Because of this persistence and strong joint commitment, finally in 2023 after the establishment of Besani Village as a tourist village in 2021, Besani Village has occupied the 75th position in ADWI.